Straddling the Boundary: The Case of Mahali Christians in Terms of their Socio-Cultural Adjustment, in Two Mahali Villages in Bangladesh - Sarker, Shahnaz; Hossain, Bokul; Sarker, Rayhena (International Journal of Asian Social Science, 2018)
In this study we selected a small ethnic group named Mahali living in the villages Pachandar and Mondumala of Barind track at Rajshahi in the north-western part of Bangladesh along with the mainstream individuals. Those two villages are entirely occupied by homogenous people of Mahali who practice their traditional lifestyle accompanied by Christianity. In this context, we have tried to explore the religious syncretism of the Mahali Christians regarding their ethnic background, socio-economic status, power structure and their belief systems. We also identify the process of acculturation that took place among the Mahalis after Christianization and that resulted in a number of social changes through decades, thus turning the Mahali culture into a state of transition. In addition, we have also made some recommendations on this issue based on the findings having from the study